NANOMEDICINES FOR PARKINSON DISEASE: CURRENT STATUS AND FUTURE PERSPECTIVE - RICHARD L JAYARAJ,; VIVEK CHANDRAMOHAN,; ELANGOVAN NAMASIVAYAM, (International Journal of Pharma and Bio Sciences, 2013)
Parkinson disease (PD) is the second most common progressive neurodegenerative disorder due to loss neurons in SubstantiaNigra pars compacta. A number of medical and surgical treatments are currently available but the beneficial effects wear off with long term use and many native therapies have severe side effects. Hence novel therapeutic strategies continue to be in the developmental demand. Nanomedicine is an important medical application in Nanotechnology which shows promising future in drug delivery system in Parkinson disease. This review gives a glimpse about current treatment for PD and discuss about the Nano-particle based drug delivery which evades Blood-Brain Barrier. BBB stands as a gateway for drug targeting in the central nervous system. Various potential nanoparticles and nanosystems based therapies are explored and benefits are heaved out. Further with a set of well regulated guidelines, it would allow nanotechnology to be used within medicine safely and people could benefit from its attributes.